Proceedings of the symposium on Disaster Risk Management - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2022)
Represents the proceedings of the symposium, with a view to sharing the presentations, discussions and recommendations to as wide an audience as possible. It is hoped that this publication can form the basis for enhanced knowledge of and information on the various initiatives – both global and regional – as they relate to the development of disaster risk management strategies for the agriculture sector in the Caribbean.